Pre-season and in-season body composition assessment by bioimpedance in professional football athletes: implications for sports nutrition, physical performance, and hormonal health - Iblasi, Rand; Abualsaud, Mahmoud; Amawi, Adam Tawfiq; Ghazzawi, Hadeel (Frontiers in Nutrition, 2025)
Seasonal transitions in professional football specifically between the pre-season and in-season phases are accompanied by distinct physiological, hormonal, and nutritional demands. Understanding these fluctuations is essential to optimizing dietary periodization, improving performance outcomes, and supporting player recovery. This study aimed to assess and compare the dietary intake, hormonal biomarkers, and body composition of professional football players during the pre-season and in-season phases. A cross-sectional observational study was conducted on 15 professional male football players (mean age: 25.15 ± 3.78 years). Dietary intake was recorded over 7 consecutive days during each phase and analyzed using ESHA Food Processor software. Nutrient adequacy was evaluated against established sports nutrition guidelines. Physical performance (30-meter sprint, vertical jump, and Yo-Yo Intermittent Recovery Test Level 1), body composition (body weight, fat mass, and fat-free mass via bioimpedance), and hormonal biomarkers (GH, IGF-1, testosterone, insulin, cortisol) were also measured. Average daily energy and carbohydrate intake were higher during the in-season phase (3,240 kcal and 392.0 g, respectively) compared to pre-season (2,890 kcal and 349.6 g), though the differences were not statistically significant (p > 0.05). Protein intake was significantly higher during pre-season (168.79 ± 42.03 g vs. 140.86 ± 34.86 g, p = 0.02), whereas fat intake was significantly lower (98.26 ± 23.32 g vs. 131.04 ± 42.74 g, p = 0.01). Micronutrient analysis revealed significant phase-dependent differences in intake of vitamins B1, B2, B5, choline, calcium, sodium, and zinc (p < 0.05). Only GH levels showed a significant increase in-season (0.49 ng/mL vs. 0.19 ng/mL, p = 0.03); no other hormonal markers differed significantly. Despite increased physical demands, players failed to meet recommended energy and carbohydrate targets in both pre-season and in-season phases, while protein intake exceeded recommendations. Several micronutrient imbalances were also observed. These findings highlight the need for tailored, phase-specific nutritional strategies to support the health, hormonal balance, and performance of professional football players throughout the competitive season.